2013
DOI: 10.1017/s0033822200048578
|View full text |Cite
|
Sign up to set email alerts
|

Early Bomb Radiocarbon Detected in Palau Archipelago Corals

Abstract: In order to evaluate the variability in surface water masses in the Western Pacific Warm Pool, we report high-precision radiocarbon measurements in annual and seasonal bands from Pontes lutea corals collected from the Palau Archipelago (7°N, 134°E). Annual coral bands from 1945 to 2008 and seasonal samples from 1953 to 1957 were analyzed to capture the initial early input of bomb 14C from surface thermonuclear weapons testing in the Marshall Islands. Results show a pre-bomb average δ14C value of-54.9% between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 12 publications
2
33
0
Order By: Relevance
“…Comparisons of amphipod Δ 14 C with the postbomb coral Δ 14 C records and with the body length. (a) Δ 14 C of tissues (diamonds) and gut contents (green circles) with temporal variations of Δ 14 C in surface seawater as recorded in banded corals from Guam (13°35.9′N, 144°50.2′E, solid red line; Andrews et al, ) and Palau (7.28°N, 134.25°E, solid black line; Glynn et al, ), DIC in WP (blue crosses; Ge et al, ), and estimation of DIC based on a decrease rate of 3.7 ± 0.1‰/year (Text S2 in the supporting information). (b) Least squares relationship (solid line) between the Δ 14 C values and amphipod body lengths, r 2 = 0.89.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons of amphipod Δ 14 C with the postbomb coral Δ 14 C records and with the body length. (a) Δ 14 C of tissues (diamonds) and gut contents (green circles) with temporal variations of Δ 14 C in surface seawater as recorded in banded corals from Guam (13°35.9′N, 144°50.2′E, solid red line; Andrews et al, ) and Palau (7.28°N, 134.25°E, solid black line; Glynn et al, ), DIC in WP (blue crosses; Ge et al, ), and estimation of DIC based on a decrease rate of 3.7 ± 0.1‰/year (Text S2 in the supporting information). (b) Least squares relationship (solid line) between the Δ 14 C values and amphipod body lengths, r 2 = 0.89.…”
Section: Resultsmentioning
confidence: 99%
“…Hadal amphipods are highly dependent on surface‐derived OM, and, therefore, can be 14 C dated similarly to surface pelagic animals. The muscle tissue with the highest Δ 14 C value (65 ± 2‰) shows a result between CE 2004 and CE 2007 based on the Palau coral record (Andrews et al, ; Glynn et al, ; Ishihara et al, ; Figure a). Although the utilization of muscle tissues does not provide definite ages, they provide an estimate of the magnitude of longevity of hadal amphipods, which is longer than 10 years.…”
Section: Resultsmentioning
confidence: 99%
“…(); (i) Palau from Glynn et al . (), (j) Guam from Andrews et al . (); (k) Nauru from Guilderson et al .…”
Section: Resultsmentioning
confidence: 99%
“…() reported that in the region of the North Equatorial Current (NEC), which is the source region of the Kuroshio Current, Δ R was 78 years in the early 1900s on the basis of analyses of pre‐bomb molluscan shells from Palau and Ponape. In contrast, Δ R values obtained from Δ 14 C data on corals from Guam, Palau, Hawaii and Fanning Island in the equatorial Pacific are negative for 1945–1950 (Druffel, ; Druffel et al , ; Grottoli et al , ; Glynn et al , ; Andrews et al , ). This may be biased because the Δ R values of the 1900s shown in Table are from data for 23 years, from 1892 to 1915, whereas Δ R values in the 1940s are for 10 years, for the period from 1940 to 1950.…”
Section: Resultsmentioning
confidence: 99%
“… (a) The bomb‐ 14 C record reconstructed from M. stimpsoni shells (red) and seawater Δ 14 C values in Funakoshi Bay (blue diamonds) and Otsuchi Bay (light blue triangles). For comparison, the bomb‐ 14 C records reconstructed from reef‐building coral skeletons in the tropical to subtropical Pacific are shown: Galapagos (green, 1°S, 90°W; Druffel, ), Nauru (blue, 1°S, 167°E; Guilderson et al, ), Palau (purple, 7°N, 134°E; Glynn et al, ), and Kure Atoll (yellow, 28°N, 178°W; Andrews et al, ). Atmospheric Δ 14 C records (black lines) for the years 1930–1950 are from compiled data from INTCAL13 (Reimer et al, ); the records for the years 1950–1986 are compiled from data for the northern hemisphere (NH Zone 2; Hua et al, ); and records for the years 1986–2016 are from direct observations at Schauinsland in Germany (Hammer & Levin, ).…”
Section: Discussionmentioning
confidence: 99%